Sentinel Lymph Node Biopsy for Risk‐Reducing Mastectomy. Issue 5 (19th July 2013) - Burger, Amy; Thurtle, David; Owen, Sally; Mannu, Gurdeep; Pilgrim, Simon; Vinayagam, Raman; Pain, Simon
Abstract Risk‐reducing mastectomy (RRM) confers 90–95% decreased risk of breast cancer, and may reduce mortality, especially in high‐risk groups such as BRCA carriers. Risk of occult disease in RRM specimen is 5%. This demands axillary staging: sentinel lymph node (SLN) biopsy is no longer possible, axillary clearance confers significant risks and may prove negative. Contemporaneous SLN biopsy allows axillary staging with minimal further dissection. Women undergoing RRM and SLN biopsy between June 2005 and July 2010 were reviewed retrospectively from our prospectively maintained database of 1, 522 SLN procedures in 1, 498 patients. SLN(s) localized using routine tracer methods. SLNs and mastectomy specimens underwent routine histologic examination. Eighty‐three RRMs with SLN biopsy were performed in 71 patients (12 bilateral). Indications for RRM: contralateral invasive (55), in situ (5) disease, BRCA 1/2 mutation (12), and strong family history (10). Mean number of SLNs: 1.35. Occult disease was detected in four cases (4.8%), with one case of occult invasive lobular carcinoma (1.2%). Remaining occult disease was lobular in situ neoplasia (LISN). SLNs were negative in all cases. Our findings are comparable to those in the literature: 4.8% rate of occult disease overall, 1.2% invasive. The significant risk with SLN biopsy is lymphoedema, quoted around 7%. We have had no reports of symptomatic lymphoedema in patients undergoing RRM and SLN biopsy. We propose that SLN at the time of mastectomy requires only limited further dissection, and confers minimal risk compared with secondary axillary surgery.